Hollow fiber ultrafiltration membrane as well as preparation method and application thereof

During the preparation process of hollow fiber membranes, polycondensation reaction between aldehyde compounds and metal chlorides and melamine is used to form a porous network structure and generate nanoparticles, which solves the problems of low pressure resistance and water flux of the existing hollow fiber membranes. At the same time, the hydrophilic layer is formed through cellulose, which improves the anti-pollution performance and achieves a more efficient water treatment effect.

CN119701668AActive Publication Date: 2025-03-28HANGZHOU WATER TREATMENT TECH DEV CENT
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411960991.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-28
Publication Date
2025-03-28
Estimated Expiration
2044-12-28

AI Technical Summary

Technical Problem

The existing hollow fiber membranes have a large proportion of solvents added during the preparation process, resulting in large finger-like pore structures in the membrane, poor pressure resistance, low water flux, and poor anti-pollution performance.

Method used

Hollow fiber ultrafiltration membrane was prepared by thermally induced phase separation. By adding aldehyde compounds and metal chlorides to the cast membrane liquid and reacting with melamine under alkaline conditions, a porous network structure polymer was formed; at the same time, the metal chloride in the cast membrane liquid reacted with the hydroxide in the core liquid to form nanoparticles, enhancing the water flux; cellulose was added to the cooling bath to form a hydrophilic layer, which improved the anti-pollution performance.

Benefits of technology

The pressure resistance and water flux of hollow fiber ultrafiltration membrane are improved, while enhancing its anti-pollution performance, making it more suitable for water treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701668A_ABST
    Figure CN119701668A_ABST
Patent Text Reader

Abstract

The invention relates to a hollow fiber ultrafiltration membrane and a preparation method and application thereof.The preparation method of the hollow fiber ultrafiltration membrane comprises the following steps that a high-molecular polymer, a pore-foaming agent and a diluent are prepared into a homogeneous membrane casting solution, the pore-foaming agent comprises an aldehyde compound and a metal chloride, and the diluent is added into the membrane casting solution; the metal chloride is selected from at least one of calcium chloride, magnesium chloride, ferric chloride and copper chloride; melamine, hydroxide and water are prepared into core liquid, and the pH value of the core liquid is 10-13; the membrane casting solution and the core solution are extruded to form a hollow fiber membrane blank, then the hollow fiber membrane blank passes through an air section and enters a cooling bath to be subjected to phase separation, curing forming and diluent removal, the hollow fiber ultrafiltration membrane is obtained, the temperature of the cooling bath is-10 DEG C to-20 DEG C, and the cooling bath comprises sodium hydroxide, urea, cellulose and water. The hollow fiber ultrafiltration membrane prepared by the preparation method has high pressure resistance and water flux, also has excellent anti-pollution performance, and can be better applied to water treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water treatment membranes, in particular to a hollow fiber ultrafiltration membrane and a preparation method and application thereof. Background Art

[0002] Most of the existing polysulfone or polyethersulfone hollow fiber membranes are prepared by non-solvent phase separation. However, in this preparation method, a large proportion of solvent is usually added to the casting solution, and the prepared hollow fiber membrane has a large finger-like pore structure inside, which makes the pressure resistance of the hollow fiber membrane poor, and the dense cortex is thick, resulting in a low water flux of the hollow fiber membrane. In addition, the existing hollow fiber membrane also has the problem of poor anti-pollution performance. Summary of the invention

[0003] Based on this, it is necessary to provide a hollow fiber ultrafiltration membrane and its preparation method and application to address the above problems. The hollow fiber ultrafiltration membrane prepared by this preparation method has high pressure resistance and water flux, and at the same time has excellent anti-pollution performance, and can be better used in water treatment.

[0004] A method for preparing a hollow fiber ultrafiltration membrane comprises the following steps:

[0005] A high molecular polymer, a porogen and a diluent are prepared into a homogeneous casting solution, wherein the porogen comprises an aldehyde compound and a metal chloride, and the metal chloride is selected from at least one of calcium chloride, magnesium chloride, ferric chloride and cupric chloride;

[0006] Prepare a core liquid by mixing melamine, hydroxide and water, wherein the pH value of the core liquid is 10-13;

[0007] The casting liquid and the core liquid are extruded to form a hollow fiber membrane embryo, and then the hollow fiber membrane embryo passes through an air section and enters a cooling bath to undergo phase separation and solidification, and the diluent is removed to obtain a hollow fiber ultrafiltration membrane, wherein the temperature of the cooling bath is -10°C to -20°C, and the cooling bath includes sodium hydroxide, urea, cellulose and water.

[0008] In one embodiment, the mass fraction of the high molecular weight polymer in the casting solution is 15%-20%;

[0009] And / or, the mass fraction of the porogen in the casting solution is 1.5%-7%;

[0010] And / or, the mass fraction of the aldehyde compound in the casting solution is 1%-3%;

[0011] And / or, the mass fraction of the metal chloride in the casting solution is 0.5%-1%.

[0012] In one embodiment, the mass fraction of melamine in the core liquid is 1%-5%;

[0013] And / or, the mass fraction of the hydroxide in the core liquid is 0.5%-1.5%.

[0014] In one embodiment, the mass fraction of the sodium hydroxide in the cooling bath is 7%-10%;

[0015] And / or, the mass fraction of urea in the cooling bath is 12%-15%;

[0016] And / or, the mass fraction of the cellulose in the cooling bath is 0.5%-2.5%.

[0017] In one embodiment, the high molecular polymer is selected from at least one of polysulfone, polyethersulfone, polyetherketone and polyacrylonitrile;

[0018] And / or, the diluent is at least one selected from N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide;

[0019] And / or, the porogen further comprises an auxiliary agent, and the auxiliary agent is selected from at least one of polyvinyl pyrrolidone, alcohols, lithium chloride, and potassium chloride;

[0020] And / or, the aldehyde compound is at least one selected from formaldehyde, acetaldehyde, glyoxal, and glutaraldehyde.

[0021] In one embodiment, the hydroxide is selected from sodium hydroxide and / or potassium hydroxide;

[0022] And / or, the core liquid further includes an additive, and the additive is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, glycerol, N-methylpyrrolidone, ethanol, and dimethyl sulfoxide.

[0023] In one embodiment, the mass fraction of the additive in the core liquid is 1.5%-6.5%.

[0024] In one embodiment, the method for preparing the casting solution comprises the following steps: mixing the high molecular weight polymer, the porogen and the diluent, stirring and dissolving at 120°C-160°C for 20h-50h, and then vacuum degassing at 120°C-160°C for 8h-10h to obtain the casting solution;

[0025] And / or, the length of the air segment is 15cm-20cm.

[0026] A hollow fiber ultrafiltration membrane is prepared by the hollow fiber ultrafiltration membrane preparation method as described above.

[0027] An application of the hollow fiber ultrafiltration membrane as described above in water treatment equipment.

[0028] In the preparation method of the hollow fiber ultrafiltration membrane of the present invention, in the process of extruding the casting liquid and the core liquid to form a hollow fiber membrane embryo, the casting liquid and the core liquid are in contact, and the aldehyde compounds in the casting liquid and the melamine in the core liquid undergo a polycondensation reaction under alkaline conditions to form a porous network structure polymer, which is interspersed in the hollow fiber membrane embryo and can effectively regulate the pore size distribution of the hollow fiber ultrafiltration membrane, thereby effectively improving the pressure resistance of the hollow fiber ultrafiltration membrane and facilitating the improvement of the water flux of the hollow fiber ultrafiltration membrane; at the same time, the metal chloride in the casting liquid also reacts with the hydroxide in the core liquid to generate nanoparticles And dispersed in the hollow fiber membrane embryo, the presence of the nanoparticles can effectively increase the water production channel of the hollow fiber ultrafiltration membrane, and further improve the water flux of the hollow fiber ultrafiltration membrane; at the same time, in the cooling bath, the porogen and diluent in the casting solution will diffuse into the cooling bath, so that the high molecular polymer is precipitated and solidified, so that the hollow fiber membrane embryo forms a hollow fiber ultrafiltration membrane, and in this process, since the cooling bath is a cellulose solution, the surface of the hollow fiber ultrafiltration membrane can be wrapped with a cellulose layer, and the hydrophilic modification of the hollow fiber ultrafiltration membrane is achieved, thereby improving the hydrophilic performance of the hollow fiber ultrafiltration membrane, thereby improving the anti-pollution performance of the hollow fiber ultrafiltration membrane. Therefore, the hollow fiber ultrafiltration membrane prepared by the present invention has high pressure resistance and water flux, and has excellent anti-pollution performance, and can be better used in water treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 This is an electron microscope image of the hollow fiber ultrafiltration membrane prepared in Example 1 of the present invention;

[0031] Figure 2 for Figure 1 A partial enlarged view of the hollow fiber ultrafiltration membrane;

[0032] Figure 3 This is an electron microscope image of the hollow fiber ultrafiltration membrane prepared in Comparative Example 1 of the present invention;

[0033] Figure 4 This is an electron microscope image of the hollow fiber ultrafiltration membrane prepared in Comparative Example 3 of the present invention;

[0034] Figure 5 This is an electron microscope image of the hollow fiber ultrafiltration membrane prepared in Comparative Example 4 of the present invention;

[0035] Figure 6 This is an electron microscope image of the hollow fiber ultrafiltration membrane prepared in Comparative Example 5 of the present invention;

[0036] Figure 7 This is an electron microscope image of the hollow fiber ultrafiltration membrane prepared in Comparative Example 10 of the present invention. DETAILED DESCRIPTION

[0037] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.

[0039] The method for preparing the hollow fiber ultrafiltration membrane provided by the present invention comprises the following steps:

[0040] A high molecular polymer, a porogen and a diluent are prepared into a homogeneous casting solution, wherein the porogen comprises an aldehyde compound and a metal chloride, and the metal chloride is selected from at least one of calcium chloride, magnesium chloride, ferric chloride and cupric chloride;

[0041] Prepare a core liquid by mixing melamine, hydroxide and water, wherein the pH value of the core liquid is 10-13;

[0042] The casting liquid and the core liquid are extruded to form a hollow fiber membrane embryo, and then the hollow fiber membrane embryo passes through an air section and enters a cooling bath to undergo phase separation and solidification, and the diluent is removed to obtain a hollow fiber ultrafiltration membrane, wherein the temperature of the cooling bath is -10°C to -20°C, and the cooling bath includes sodium hydroxide, urea, cellulose and water.

[0043] In the present invention, a thermally induced phase separation method is used to prepare a hollow fiber ultrafiltration membrane. Specifically, in the process of extruding the casting liquid and the core liquid to form a hollow fiber membrane embryo, the casting liquid and the core liquid are in contact. Since the pH value of the core liquid is 10-13, the aldehyde compounds in the casting liquid can undergo a condensation reaction with the melamine in the core liquid to form a porous network structure polymer. The porous network structure polymer will be interspersed in the hollow fiber membrane embryo, which can effectively regulate the pore size distribution of the hollow fiber ultrafiltration membrane and improve its porosity, thereby effectively improving the pressure resistance of the hollow fiber ultrafiltration membrane and helping to improve the water flux of the hollow fiber ultrafiltration membrane; at the same time, the metal chloride in the casting liquid will also react with the hydroxide in the core liquid to generate nanoparticles and disperse in the hollow fiber membrane embryo. The presence of the nanoparticles can effectively increase the water production channel of the hollow fiber ultrafiltration membrane and further improve the water flux of the hollow fiber ultrafiltration membrane.

[0044] When the hollow fiber membrane embryo passes through the air section and enters the cooling bath to undergo phase separation and solidify into shape, in the cooling bath, the porogen and diluent in the casting liquid will diffuse into the cooling bath, causing the high molecular polymer to precipitate and solidify into shape, so that the hollow fiber membrane embryo forms a hollow fiber ultrafiltration membrane with higher porosity. At the same time, in this process, since the cooling bath is a cellulose solution, cellulose will adhere to the surface of the hollow fiber ultrafiltration membrane to form a cellulose layer by utilizing the characteristics of cellulose being hydrophilic and insoluble in water, thereby achieving hydrophilic modification of the hollow fiber ultrafiltration membrane, thereby improving the hydrophilic properties of the hollow fiber ultrafiltration membrane, thereby improving the anti-pollution performance of the hollow fiber ultrafiltration membrane.

[0045] Therefore, the hollow fiber ultrafiltration membrane prepared by the present invention has high pressure resistance and water flux, and also has excellent anti-pollution performance, and can be better applied in water treatment.

[0046] Optionally, the mass fraction of the high molecular weight polymer in the casting solution is 15%-20%. With such a configuration, the membrane structure and performance of the hollow fiber ultrafiltration membrane can be adjusted by regulating the amount of the high molecular weight polymer.

[0047] Furthermore, the high molecular polymer is selected from at least one of polysulfone, polyethersulfone, polyetherketone and polyacrylonitrile, preferably polysulfone and / or polyethersulfone; such arrangement is beneficial to improving the mechanical properties and chemical resistance of the hollow fiber ultrafiltration membrane.

[0048] Optionally, the mass fraction of the porogen in the casting solution is 1.5%-7%; by such a setting, the porosity of the hollow fiber ultrafiltration membrane can be regulated by adjusting the dosage of the porogen, thereby improving the continuity of the hollow fiber ultrafiltration membrane pores and further improving the water flux of the hollow fiber ultrafiltration membrane.

[0049] Optionally, the mass fraction of the aldehyde compound in the casting liquid is 1%-3%; the mass fraction of the melamine in the core liquid is 1%-5%; such an arrangement, by controlling the amount of the aldehyde compound in the casting liquid and the melamine in the core liquid, is conducive to allowing the aldehyde compound and melamine to undergo sufficient condensation polymerization to generate a polymer with a porous network structure, which can better adjust the membrane structure of the hollow fiber ultrafiltration membrane, thereby improving the mechanical properties and water flux of the hollow fiber ultrafiltration membrane.

[0050] Furthermore, the aldehyde compound is selected from at least one of formaldehyde, acetaldehyde, glyoxal and glutaraldehyde.

[0051] In the present invention, the porogen further comprises an auxiliary agent, and the auxiliary agent is selected from at least one of polyvinyl pyrrolidone, alcohols, lithium chloride and potassium chloride.

[0052] In one embodiment, the mass fraction of the auxiliary agent in the casting solution is 1%-3%.

[0053] Optionally, the diluent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide.

[0054] Optionally, the mass fraction of the metal chloride in the casting liquid is 0.5%-1%; the mass fraction of the hydroxide in the core liquid is 0.5%-1.5%; by such arrangement, by controlling the amount of metal chloride in the casting liquid and the amount of hydroxide in the core liquid, the amount of nanoparticles formed can be controlled, which is conducive to better dispersion of the nanoparticles in the hollow fiber ultrafiltration membrane, and further improves the water flux of the hollow fiber ultrafiltration membrane; at the same time, by controlling the amount of hydroxide in the core liquid, the pH value of the core liquid can also be better regulated to further ensure the condensation reaction of melamine in the core liquid and aldehyde compounds in the casting liquid.

[0055] Furthermore, the hydroxide is selected from sodium hydroxide and / or potassium hydroxide.

[0056] In the present invention, the core liquid further comprises an additive, and the additive is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, glycerol, N-methylpyrrolidone, ethanol, and dimethyl sulfoxide.

[0057] Furthermore, the mass fraction of the additive in the core liquid is 1.5%-6.5%.

[0058] Optionally, the mass fraction of the cellulose in the cooling bath is 0.5%-2.5%; such a configuration is conducive to forming a uniform hydrophilic cellulose layer on the surface of the hollow fiber ultrafiltration membrane, further improving the hydrophilicity of the hollow fiber ultrafiltration membrane, and then better improving the anti-pollution performance of the hollow fiber ultrafiltration membrane.

[0059] Optionally, the mass fraction of the sodium hydroxide in the cooling bath is 7%-10%; the mass fraction of the urea in the cooling bath is 12%-15%. Such an arrangement can better achieve rapid dissolution of cellulose to form a stable cellulose solution.

[0060] In the present invention, the preparation method of the casting solution comprises the following steps: mixing the high molecular polymer, the porogen and the diluent, stirring and dissolving at 120°C-160°C for 20h-50h, and then vacuum degassing at 120°C-160°C for 8h-10h to obtain the casting solution.

[0061] In one embodiment, the stirring speed is 80 rpm-120 rpm.

[0062] In one embodiment, the high molecular polymer is in a dry state. This configuration can avoid the influence of the water contained in the high molecular polymer on the composition of the casting solution.

[0063] Optionally, the length of the air segment is 15cm-20cm.

[0064] In one embodiment, the diluent is removed by using an extractant, specifically, the solidified hollow fiber ultrafiltration membrane is immersed in the extractant to extract the diluent, wherein the extractant is preferably water. It is understood that in this process, unreacted porogens can also be removed to obtain a cleaned hollow fiber ultrafiltration membrane.

[0065] In one embodiment, the casting solution and the core solution are injected into a tube-type spinneret by dry-wet spinning equipment, and are extruded from the spinneret together to form a hollow fiber membrane embryo, wherein the spinning speed is 16m / min-18m / min.

[0066] In one embodiment, before the casting solution and the core solution are extruded to form the hollow fiber membrane embryo, the casting solution is filtered using a filter screen with 250-350 meshes.

[0067] At the same time, the present invention also provides a hollow fiber ultrafiltration membrane prepared by the method for preparing the hollow fiber ultrafiltration membrane as described above. The hollow fiber ultrafiltration membrane has high pressure resistance and water flux, and also has excellent anti-pollution performance, and can be better applied to water treatment.

[0068] In addition, the present invention also provides a use of the hollow fiber ultrafiltration membrane as described above in a water treatment device.

[0069] In one embodiment, the water treatment device may be a water purification device.

[0070] The hollow fiber ultrafiltration membrane and its preparation method and application will be further described below by the following specific examples. However, those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0071] Example 1

[0072] Polysulfone (dry state), formaldehyde, magnesium chloride and N,N-dimethylformamide are placed in a stirring tank, and then stirred at 130°C and a rotation speed of 100 rpm for 20 hours, and then vacuum degassed at 120°C for 10 hours to obtain a homogeneous casting liquid, wherein in the casting liquid, the mass fraction of polysulfone is 18%, the mass fraction of formaldehyde is 2%, and the mass fraction of magnesium chloride is 0.7%; melamine, sodium hydroxide and water are prepared into a core liquid, wherein in the core liquid, the mass fraction of melamine is 3%, the mass fraction of sodium hydroxide is 1%, and the pH value of the core liquid is about 12.5; sodium hydroxide, urea, cellulose and water are prepared into a cooling bath, wherein in the cooling bath, the mass fraction of sodium hydroxide is 8%, the mass fraction of urea is 13%, the mass fraction of cellulose is 1.2%, and the temperature of the cooling bath is controlled to be -15°C.

[0073] The casting solution and the core solution obtained above were injected into a tube-type spinneret by dry-wet spinning equipment, and extruded from the spinneret together to form a hollow fiber membrane embryo, wherein the spinning speed was 18 m / min; the hollow fiber membrane embryo passed through a 15 cm air section, entered a -15°C cooling bath to undergo phase separation and solidification, and finally immersed in 40°C pure water for extraction treatment for 36 hours to obtain the following: Figure 1-Figure 2 The hollow fiber ultrafiltration membrane shown.

[0074] Example 2

[0075] Polyethersulfone (dry state), glyoxal, calcium chloride and N,N-dimethylacetamide are placed in a stirring tank, and then stirred at 120°C and a rotation speed of 100 rpm for 30 hours, and then vacuum degassed at 140°C for 9 hours to obtain a homogeneous casting liquid, wherein in the casting liquid, the mass fraction of polyethersulfone is 15%, the mass fraction of glyoxal is 1%, and the mass fraction of calcium chloride is 0.5%; melamine, potassium hydroxide and water are prepared into a core liquid, wherein in the core liquid, the mass fraction of melamine is 1%, the mass fraction of potassium hydroxide is 0.5%, and the pH value of the core liquid is about 10; sodium hydroxide, urea, cellulose and water are prepared into a cooling bath, wherein in the cooling bath, the mass fraction of sodium hydroxide is 7%, the mass fraction of urea is 12%, the mass fraction of cellulose is 0.5%, and the temperature of the cooling bath is controlled to be -10°C.

[0076] The casting liquid and core liquid obtained above were injected into a tube-type spinneret by dry-wet spinning equipment, and extruded from the spinneret together to form a hollow fiber membrane embryo, wherein the spinning speed was 18 m / min; the hollow fiber membrane embryo passed through an 18 cm air section, entered a -10°C cooling bath to undergo phase separation and solidification, and finally immersed in 40°C pure water for extraction treatment for 36 hours to obtain a hollow fiber ultrafiltration membrane.

[0077] Example 3

[0078] Polyether ketone (dry state), glutaraldehyde, ferric chloride and dimethyl sulfoxide are placed in a stirring tank, and then stirred at 160°C at a rotation speed of 100 rpm for 25 hours, and then vacuum degassed at 160°C for 8 hours to obtain a homogeneous casting liquid, wherein in the casting liquid, the mass fraction of the polyether ketone is 20%, the mass fraction of the glutaraldehyde is 3%, and the mass fraction of the ferric chloride is 1%; melamine, sodium hydroxide and water are prepared into a core liquid, wherein in the core liquid, the mass fraction of melamine is 5%, the mass fraction of sodium hydroxide is 1.5%, and the pH value of the core liquid is about 13; sodium hydroxide, urea, cellulose and water are prepared into a cooling bath, wherein in the cooling bath, the mass fraction of sodium hydroxide is 10%, the mass fraction of urea is 15%, the mass fraction of cellulose is 2.5%, and the temperature of the cooling bath is controlled to be -20°C.

[0079] The casting liquid and core liquid obtained above were injected into a tube-type spinneret by dry-wet spinning equipment, and extruded from the spinneret together to form a hollow fiber membrane embryo, wherein the spinning speed was 18 m / min; the hollow fiber membrane embryo passed through a 20 cm air section, entered a -20°C cooling bath to undergo phase separation and solidification, and finally immersed in 40°C pure water for extraction treatment for 36 hours to obtain a hollow fiber ultrafiltration membrane.

[0080] Example 4

[0081] Compared with Example 1, Example 4 differs only in that the mass fraction of polysulfone in the casting solution is 12%, and other conditions are the same to obtain a hollow fiber ultrafiltration membrane.

[0082] Example 5

[0083] Compared with Example 1, Example 5 differs only in that the mass fraction of polysulfone in the casting solution is 25%, and other conditions are the same to obtain a hollow fiber ultrafiltration membrane.

[0084] Example 6

[0085] Compared with Example 1, Example 6 differs only in that the mass fraction of formaldehyde in the casting solution is 0.05%, and other conditions are the same to obtain a hollow fiber ultrafiltration membrane.

[0086] Example 7

[0087] Compared with Example 1, Example 7 differs only in that the mass fraction of formaldehyde in the casting solution is 5%, and other conditions are the same, thereby obtaining a hollow fiber ultrafiltration membrane.

[0088] Example 8

[0089] Compared with Example 1, Example 8 differs only in that the mass fraction of magnesium chloride in the casting solution is 0.1%, and other conditions are the same to obtain a hollow fiber ultrafiltration membrane.

[0090] Example 9

[0091] The only difference between Example 9 and Example 1 is that the mass fraction of magnesium chloride in the casting solution is 2%, and the other conditions are the same, thereby obtaining a hollow fiber ultrafiltration membrane.

[0092] Example 10

[0093] The only difference between Example 10 and Example 1 is that the mass fraction of melamine in the core liquid is 0.1%, and the other conditions are the same to obtain a hollow fiber ultrafiltration membrane.

[0094] Embodiment 11

[0095] Compared with Example 1, Example 11 is different from Example 1 only in that the mass fraction of melamine in the core liquid is 6%, and other conditions are the same to obtain a hollow fiber ultrafiltration membrane.

[0096] Example 12

[0097] Compared with Example 1, Example 12 differs only in that the mass fraction of the sodium hydroxide in the core liquid is 0.1%, and the other conditions are the same, thereby obtaining a hollow fiber ultrafiltration membrane.

[0098] Embodiment 13

[0099] Compared with Example 1, Example 13 differs only in that the mass fraction of the sodium hydroxide in the core liquid is 2%, and the other conditions are the same, thereby obtaining a hollow fiber ultrafiltration membrane.

[0100] Embodiment 14

[0101] Compared with Example 1, Example 14 differs only in that the mass fraction of the sodium hydroxide in the cooling bath is 6%, and the other conditions are the same, thereby obtaining a hollow fiber ultrafiltration membrane.

[0102] Embodiment 15

[0103] Compared with Example 1, Example 15 differs only in that the mass fraction of the urea in the cooling bath is 10%, and the other conditions are the same, thereby obtaining a hollow fiber ultrafiltration membrane.

[0104] Example 16

[0105] Compared with Example 1, Example 16 differs only in that the mass fraction of the cellulose in the cooling bath is 0.1%, and other conditions are the same, thereby obtaining a hollow fiber ultrafiltration membrane.

[0106] Embodiment 17

[0107] The only difference between Example 17 and Example 1 is that the mass fraction of the cellulose in the cooling bath is 3%, and the other conditions are the same, thereby obtaining a hollow fiber ultrafiltration membrane.

[0108] Embodiment 18

[0109] Compared with Example 1, Example 18 differs only in that, in the step of preparing the casting solution, the casting solution also contains lithium chloride, and the mass fraction of the lithium chloride in the casting solution is 1%. Other conditions are the same, and a hollow fiber ultrafiltration membrane is obtained.

[0110] Embodiment 19

[0111] The only difference between Example 19 and Example 1 is that, in the step of preparing the core liquid, the core liquid also contains N,N-dimethylformamide, and the mass fraction of N,N-dimethylformamide in the core liquid is 1.5%. The other conditions are the same, and a hollow fiber ultrafiltration membrane is obtained.

[0112] Embodiment 20

[0113] The only difference between Example 20 and Example 1 is that, in the step of preparing the core liquid, the core liquid also contains glycerol, and the mass fraction of the glycerol in the core liquid is 6.5%. The other conditions are the same, and a hollow fiber ultrafiltration membrane is obtained.

[0114] Comparative Example 1

[0115] Comparative Example 1 is different from Example 1 only in that, in the step of preparing the casting solution, the casting solution does not contain formaldehyde, and the other conditions are the same, and the following is obtained: Figure 3 The hollow fiber ultrafiltration membrane shown.

[0116] Comparative Example 2

[0117] Compared with Example 1, Comparative Example 2 differs only in that, in the step of preparing the casting solution, potassium chloride is used instead of magnesium chloride, and the other conditions are the same, to obtain a hollow fiber ultrafiltration membrane.

[0118] Comparative Example 3

[0119] Comparative Example 3 is different from Example 1 only in that, in the step of preparing the casting solution, the casting solution does not contain magnesium chloride, and the other conditions are the same, and the following is obtained: Figure 4 The hollow fiber ultrafiltration membrane shown.

[0120] Comparative Example 4

[0121] Comparative Example 4 is different from Example 1 only in that, in the step of preparing the core liquid, the core liquid does not contain melamine, and the other conditions are the same, and the following is obtained: Figure 5 The hollow fiber ultrafiltration membrane shown.

[0122] Comparative Example 5

[0123] Comparative Example 5 is different from Example 1 only in that, in the step of preparing the core liquid, the core liquid does not contain sodium hydroxide, and the pH value of the core liquid is about 6.3, and the other conditions are the same, and the following is obtained: Figure 6 The hollow fiber ultrafiltration membrane shown.

[0124] Comparative Example 6

[0125] Compared with Example 1, Comparative Example 6 differs only in that, in the step of preparing the core liquid, the mass fraction of sodium hydroxide in the core liquid is 0.05%, and the pH value of the core liquid is about 8, and the other conditions are the same, and a hollow fiber ultrafiltration membrane is obtained.

[0126] Comparative Example 7

[0127] Compared with Example 1, Comparative Example 7 differs only in that, in the step of preparing the core liquid, the mass fraction of sodium hydroxide in the core liquid is 2%, and the pH value of the core liquid is about 13.8, and the other conditions are the same, and a hollow fiber ultrafiltration membrane is obtained.

[0128] Comparative Example 8

[0129] The only difference between Comparative Example 8 and Example 1 is that in the step of preparing the cooling bath, the cooling bath does not contain sodium hydroxide, urea, and cellulose. The other conditions are the same, and a hollow fiber ultrafiltration membrane is obtained.

[0130] Comparative Example 9

[0131] The only difference between Comparative Example 9 and Example 1 is that in the step of preparing the cooling bath, the cooling bath does not contain sodium hydroxide, and the other conditions are the same to obtain a hollow fiber ultrafiltration membrane.

[0132] Comparative Example 10

[0133] Comparative Example 10 is different from Example 1 only in that, in the step of preparing the cooling bath, the cooling bath does not contain urea, and the other conditions are the same, and the following is obtained: Figure 7 The hollow fiber ultrafiltration membrane shown.

[0134] Comparative Example 11

[0135] The only difference between Comparative Example 11 and Example 1 is that in the step of preparing the cooling bath, the cooling bath does not contain cellulose, and the other conditions are the same, and a hollow fiber ultrafiltration membrane is obtained.

[0136] Comparative Example 12

[0137] Compared with Example 1, Comparative Example 12 differs only in that the temperature of the cooling bath is -5°C, and the other conditions are the same, thereby obtaining a hollow fiber ultrafiltration membrane.

[0138] The inner diameter, outer diameter and porosity, dense cortex thickness, water flux, retention rate, pressure resistance and anti-pollution performance of the hollow fiber ultrafiltration membranes prepared in Examples 1-20 and Comparative Examples 1-12 were tested respectively. The test results are shown in Table 1-2. The specific test methods are as follows:

[0139] Inner diameter and outer diameter testing: tested using a scanning electron microscope.

[0140] Porosity test: The test is carried out using a scanning electron microscope and multifunctional image analysis software.

[0141] Dense cortex thickness test: tested using a scanning electron microscope.

[0142] Water flux test: The test was carried out using a membrane performance tester, where the test pressure was 0.1MPa and the inlet water was pure water.

[0143] Pressure resistance performance test: Use membrane performance tester to perform bubble point test. Specifically, seal one end of the hollow fiber ultrafiltration membrane with glue, pass gas into the other end, put the whole hollow fiber ultrafiltration membrane into water, increase the pressure, and record the pressure when bubbles appear around the hollow fiber ultrafiltration membrane. This is determined as the maximum pressure that the hollow fiber ultrafiltration membrane can withstand, that is, the corresponding pressure resistance strength is obtained.

[0144] Table 1

[0145]

[0146]

[0147] Table 2

[0148]

[0149] At the same time, the anti-pollution performance of the hollow fiber ultrafiltration membranes prepared in Examples 1-20 and Comparative Examples 1-12 was tested respectively. The test conditions were as follows: the hollow fiber ultrafiltration membrane was placed in a 1000ppm bovine serum albumin solution and placed at 40°C for 30 days, the hollow fiber ultrafiltration membrane was cleaned, and then the performance was tested under pure water as the inlet water condition. The test results are shown in Tables 3-4.

[0150] Table 3

[0151]

[0152]

[0153] Table 4

[0154]

[0155] It should be noted that in Tables 1-4, the membrane water flux (F) is calculated by the volume of water passing through the hollow fiber ultrafiltration membrane in a certain period of time, and the formula is: F = V / (A×T), wherein V is the volume of water passing through the hollow fiber ultrafiltration membrane per unit time, A is the effective membrane area, and T is time.

[0156] The calculation formula of the water flux recovery rate is: (pure water flux of the hollow fiber ultrafiltration membrane after pollution / pure water flux of the initial hollow fiber ultrafiltration membrane)×100%.

[0157] from Figure 1-Figure 2 It can be seen that the pore size distribution of the hollow fiber ultrafiltration membrane prepared in Example 1 of the present invention is relatively uniform and the porosity is relatively high; Figure 3 It can be seen that the hollow fiber ultrafiltration membrane prepared in Comparative Example 1 does not contain formaldehyde in the casting solution, so it is impossible to form a polymer with a porous network structure, so that the porosity of the hollow fiber ultrafiltration membrane is low and the pore size is small; Figure 4It can be seen that the hollow fiber ultrafiltration membrane prepared in Comparative Example 3 cannot form nanoparticles because the casting solution does not contain magnesium chloride, resulting in a lower porosity and a denser hollow fiber ultrafiltration membrane, indicating that the formation of nanoparticles has a greater impact on the porosity; Figure 5 It can be seen that the hollow fiber ultrafiltration membrane prepared in Comparative Example 4 does not contain melamine in the core liquid, and therefore, a polymer with a porous network structure cannot be formed, resulting in a low porosity and a dense hollow fiber ultrafiltration membrane. Figure 6 It can be seen that the hollow fiber ultrafiltration membrane prepared in Comparative Example 5 does not contain sodium hydroxide in the core liquid, and the core liquid is close to weak acidity, which causes formaldehyde and melamine to be unable to react, resulting in a low porosity of the hollow fiber ultrafiltration membrane; Figure 7 It can be seen that the hollow fiber ultrafiltration membrane prepared in Comparative Example 10 does not have urea added, which causes the cellulose to be insoluble and deposited on the tube wall, and the porosity and pore size of the hollow fiber ultrafiltration membrane are slightly increased.

[0158] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0159] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a hollow fiber ultrafiltration membrane, characterized in that: The steps include: A high molecular polymer, a porogen and a diluent are prepared into a homogeneous casting solution, wherein the porogen comprises an aldehyde compound and a metal chloride, and the metal chloride is selected from at least one of calcium chloride, magnesium chloride, ferric chloride and cupric chloride; Prepare a core liquid by mixing melamine, hydroxide and water, wherein the pH value of the core liquid is 10-13; The casting liquid and the core liquid are extruded to form a hollow fiber membrane embryo, and then the hollow fiber membrane embryo passes through an air section and enters a cooling bath to undergo phase separation and solidification, and the diluent is removed to obtain a hollow fiber ultrafiltration membrane, wherein the temperature of the cooling bath is -10°C to -20°C, and the cooling bath includes sodium hydroxide, urea, cellulose and water.

2. The method for preparing a hollow fiber ultrafiltration membrane according to claim 1, characterized in that: The mass fraction of the high molecular weight polymer in the casting solution is 15%-20%; And / or, the mass fraction of the porogen in the casting solution is 1.5%-7%; And / or, the mass fraction of the aldehyde compound in the casting solution is 1%-3%; And / or, the mass fraction of the metal chloride in the casting solution is 0.5%-1%.

3. The method for preparing a hollow fiber ultrafiltration membrane according to claim 1, characterized in that: The mass fraction of the melamine in the core liquid is 1%-5%; And / or, the mass fraction of the hydroxide in the core liquid is 0.5%-1.5%.

4. The method for preparing a hollow fiber ultrafiltration membrane according to claim 1, characterized in that: The mass fraction of the sodium hydroxide in the cooling bath is 7%-10%; And / or, the mass fraction of urea in the cooling bath is 12%-15%; And / or, the mass fraction of the cellulose in the cooling bath is 0.5%-2.5%.

5. The method for preparing a hollow fiber ultrafiltration membrane according to any one of claims 1 to 4, characterized in that: The high molecular polymer is selected from at least one of polysulfone, polyethersulfone, polyetherketone and polyacrylonitrile; And / or, the diluent is at least one selected from N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide; And / or, the porogen further comprises an auxiliary agent, and the auxiliary agent is selected from at least one of polyvinyl pyrrolidone, alcohols, lithium chloride, and potassium chloride; And / or, the aldehyde compound is at least one selected from formaldehyde, acetaldehyde, glyoxal, and glutaraldehyde.

6. The method for preparing a hollow fiber ultrafiltration membrane according to any one of claims 1 to 4, characterized in that: The hydroxide is selected from sodium hydroxide and / or potassium hydroxide; And / or, the core liquid further includes an additive, and the additive is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, glycerol, N-methylpyrrolidone, ethanol, and dimethyl sulfoxide.

7. The method for preparing a hollow fiber ultrafiltration membrane according to claim 6, characterized in that: The mass fraction of the additive in the core liquid is 1.5%-6.5%.

8. The method for preparing a hollow fiber ultrafiltration membrane according to any one of claims 1 to 4, characterized in that: The preparation method of the casting solution comprises the following steps: mixing the high molecular polymer, the porogen and the diluent, stirring and dissolving at 120° C.-160° C. for 20 h-50 h, and then vacuum degassing at 120° C.-160° C. for 8 h-10 h to obtain the casting solution; And / or, the length of the air segment is 15cm-20cm.

9. A hollow fiber ultrafiltration membrane prepared by the method for preparing a hollow fiber ultrafiltration membrane according to any one of claims 1 to 8.

10. Use of the hollow fiber ultrafiltration membrane according to claim 9 in water treatment equipment.

Citation Information

Patent Citations

  • Dynamic-crosslinking preparation method of polyvinyl alcohol-blended hollow-fiber ultrafiltration membrane

    CN103349920A

  • Polyamide / COFs hybridized nanofiltration composite membrane and preparation method thereof

    CN105642133A

  • Preparation method of pennisetum sinese nanofiber hollow fiber nanofiltration membrane

    CN114797501A

  • One-step method hollow fiber nanofiltration membrane forming composition and use method thereof

    CN115253707A

  • Cellulose hollow fiber membrane and its production

    JP1998216489A